FRI0235 PHASE 1 CLINICAL STUDY OF MGTA-145 IN COMBINATION WITH PLERIXAFOR SHOWS RAPID SINGLE-DAY MOBILISATION AND COLLECTION OF CD34+ HAEMATOPOIETIC STEM CELLS WITHOUT G-CSF. (2nd June 2020) - Dipersio, J.; Devine, S.; Hoggatt, J.; Scadden, D.; Howell, H.; Schmelmer, V.; Neale, J.; Boitano, T.; Cooke, M.; Morrow, D.; Raffel, G.; Savage, W.; et al.
Abstract : Background: Autologous haematopoietic stem cell (HSC) transplantation is a recommended therapeutic option for selected patients with autoimmune diseases. G-CSF mobilisation of HSCs requires 4-7 days of injections that are associated with significant side effects and potential for severe complications including disease flares (e.g., scleroderma and multiple sclerosis). MGTA-145 is a biologic that activates CXCR2 on neutrophils, and with plerixafor rapidly mobilises HSCs in mice and non-human primates. The combination promises to be a same-day, G-CSF-free mobilisation regimen. Objectives: To evaluate the safety, tolerability, and mobilisation efficacy of MGTA-145 monotherapy and combination therapy with plerixafor in healthy volunteers. Methods: This healthy volunteer phase 1 study consisted of 4 parts- Part A: single-agent MGTA-145 or placebo; Part B: MGTA-145 or placebo given immediately or 2 hours after plerixafor; Part C: MGTA-145 or placebo given 2 hours after plerixafor on 2 consecutive days; Part D: MGTA-145 given 2 hours after plerixafor, just prior to apheresis cell collection. Results: Monotherapy of MGTA-145 mobilised CD34+ cells within minutes and peaked within 1 hour post MGTA-145 (median 11 CD34+ cells/µL, a 7-fold increase vs baseline). White blood cells and neutrophils followed a similar pattern. Importantly, markers of neutrophil activation were relatively unchanged (≤2-fold vs baseline). MGTA-145 combined with plerixafor increased CD34+ cell mobilisation, whether given simultaneously or 2h after plerixafor (Fig. 1A ). Mobilisation was highly enriched for CD34+CD90+CD45RA- HSCs, which tracked closely with the total CD34 count. At the 0.03 mg/kg dose with 2h stagger, median peak CD34+ peripheral blood mobilisation was ≥40 cells/µL in Part B. On a second consecutive day of dosing, MGTA-145 + plerixafor mobilises HSCs to levels comparable to day 1. Initial data from the ongoing Part D show that sufficient numbers of cells (median 4.3 x 10^6 CD34+ cells/kg) for transplant were collected in a single day.. Preliminary data from NSG mouse transplant studies of those mobilised HSCs in part D show higher engraftment rates of MGTA-145 + plerixafor mobilised HSCs, compared to G-CSF-mobilised HSCs. MGTA-145 monotherapy was well tolerated with no significant adverse events (AEs). Grade 1, transient lower back pain that dissipated within minutes was reported. The combination of MGTA-145 with plerixafor was well tolerated, with some subjects experiencing grade 1/2 gastrointestinal AEs commonly observed with plerixafor and one grade 2 back pain with MGTA-145 at 0.075 mg/kg that resolved within minutes. Conclusion: MGTA-145 monotherapy was well-tolerated and induced rapid mobilisation of significant numbers of HSCs. CD34+ cell mobilisation with MGTA-145 + plerixafor was immediate and superior to plerixafor alone. These data suggest that the combination can enable the collection of sufficient HSCs for transplant in one day without the need for G-CSF. Further development as a first line mobilisation product is warranted in autoimmune diseases, gene therapy and haematologic malignancies. Disclosure of Interests: John Dipersio Shareholder of: Magenta, Consultant of: Cellworks, Tioma, Rivervest, Bioline, Asterias, Amphivena and Bluebird, Celgene, Incyte, NeoImuneTech, Macrogenics, Steven Devine: None declared, Jonathan Hoggatt Shareholder of: Magenta, Grant/research support from: Magenta, Consultant of: Magenta, David Scadden Shareholder of: Magenta, Consultant of: Magenta, Haley Howell Shareholder of: Magenta, Employee of: Magenta, Veit Schmelmer Shareholder of: Magenta, Employee of: Magenta, Jason Neale Shareholder of: Magenta, Employee of: Magenta, Tony Boitano Shareholder of: Magenta, Employee of: Magenta, Michael Cooke Shareholder of: Magenta, Employee of: Magenta, Dwight Morrow Shareholder of: Magenta, Employee of: Magenta, Glen Raffel Shareholder of: Magenta, Employee of: Magenta, Will Savage Shareholder of: Magenta, Employee of: Magenta, Kevin Goncalves Shareholder of: Magenta, Employee of: Magenta, Pat Falahee Shareholder of: Magenta, Employee of: Magenta, John Davis Shareholder of: Magenta, Employee of: Magenta